A possível articulação entre competências e cultura organizacional no setor cimenteiro: um estudo em empresas de serviços de concretagem - Reginaldo de Jesus Carvalho Lima (2013)
This thesis discusses the possible connection between competency and organizational culture in concrcting companies in the cement sector considering different perspectives and nuances that the debate carries. These companies face the double challenge of offering products andservices in a highly competitive market. The methodology involved three complementary phases. At first, it started case study in representative tirm in the industry, having been the data collected through interviews, observation and document analysis. The second stage comprised a survey with the companies of the Brazilian Association of Concrcting Services (ABESC) located in the states of Minas Gerais, Rio de Janeiro and Sao Paulo. ln this phase, data were collected through interviews with managers and a questionnaire for key occupations. ln these phases were characterized following analytical categories identified a priori: 1) contextual Challenges; 2) concept of competence; 3) HR Process; 4 organization of work process; 5) role of organizational culture in building competency. The third phase consisted in deepening the case study and data were collected through interviews, observation and document analysis. lt sought to understand how the link between competency andorganizational culture occurs in view ofthe following components; l) artifacts; 2) values; 3) beliefs. The survey data were treated using the software NVivo 1O and PASW Statistic 18. The results revealed that the link between organizational culture and competency relevant to the management of the workforce and permeates the structural dimensions, formative and relational organizations. Organizational culture is considered a strategic factor for the formation and shaping of labor. The link between competency and culture has its genesis in the actual production system that requires workers how to be, printing paper relevant to the culture in thc workplace, in that it is made possible by learning the necessary knowledge. As noted in case study, this articulation involves different levels and components of the culture,materializing in management practices and the dynamics ofwork.